2020
DOI: 10.1002/ptr.6883
|View full text |Cite
|
Sign up to set email alerts
|

Roles of plant‐derived bioactive compounds and relatedmicroRNAsin cancer therapy

Abstract: Plant-derived bioactive compounds, often called phytochemicals, are active substances extracted from different plants. These bioactive compounds can release therapeutic potential abilities via reducing antitumor drugs side effects or directly killing cancer cells, and others also can adjust cancer initiation and progression via regulating microRNAs (miRNAs) expression, and miRNA can regulate protein-coding expression by restraining translation or degrading target mRNA. A mass of research showed that plant-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Regulation of functions and other genes during protein synthesis is regulated by miRNA. A number of phytochemicals have been described as molecules that efficiently affect miRNAs activity in the processes of carcinogenesis [82][83][84]. Numerous miRNAs have been applied as valid biomarkers in breast cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of functions and other genes during protein synthesis is regulated by miRNA. A number of phytochemicals have been described as molecules that efficiently affect miRNAs activity in the processes of carcinogenesis [82][83][84]. Numerous miRNAs have been applied as valid biomarkers in breast cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…plant varieties. Over the past few decades, natural compounds of plant-based origin have been extensively studied as an exciting class of pharmacologically active molecules [ [22] , [23] , [24] ]. In particular, many natural products have demonstrated potent activity against CoVs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside its antiinflammatory, antiviral, antioxidant, and neuroprotective properties, antitumor effects of this natural bioactive have drawn considerable attention in phytotherapy research against breast cancer (Li et al, 2019; Lin et al, 2018), lung cancer (Liao et al, 2019), leukemia, gastrointestinal cancers, and glioma (reviewed by Fang et al, 2021). Furthermore, the interplay of Tanshinones and miRNA in exerting these anticancer effects has been highlighted recently (Zou et al, 2021). You, He, Wang, Mao, and Zhang (2020) showed that TIIA suppresses glioma cell proliferation, migration, and invasion in vitro through upregulating miR‐16‐5p.…”
Section: Natural Products and Mirnas In Glioma Therapymentioning
confidence: 99%